Comparison of gut microbiota composition between laboratory‐bred marmosets (Callithrix jacchus) with chronic diarrhea and healthy animals using terminal restriction fragment length polymorphism analysis. (21st November 2018) - Shigeno, Yuko; Toyama, Mutsumi; Nakamura, Mutsumi; Niimi, Kimie; Takahashi, Eiki; Benno, Yoshimi
ABSTRACT: Chronic diarrhea in laboratory‐bred marmosets poses a serious health problem during experiments. Despite a growing demand for laboratory‐bred experimental marmosets, the mechanisms underlying the development of diarrhea and measures for its treatment and prevention remain unclear. To explore the factors affecting development of chronic diarrhea in laboratory‐bred marmosets, the gut microbiota composition (GMC) of 58 laboratory‐bred marmosets, including 19 animals with chronic diarrhea, was analyzed using terminal restriction fragment length polymorphism. We found that the GMCs in these animals cluster into two groups that differ significantly in rate of chronic diarrhea (56.5% in one group, Cluster 1, and 17.1% in Cluster 2). Additionally, a higher α‐diversity and a lower proportion of Bifidobacterium spp. according to quantitative PCR was found the animals in the Cluster 1 than in those in Cluster 2. Taken together, our findings indicate that there is a relationship between GMC and development of chronic diarrhea in laboratory‐bred marmosets. This is the first study to highlight the potential of assessing GMC in relation to development of chronic diarrhea in laboratory‐bred marmosets.